2020
DOI: 10.1186/s40816-020-00218-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of peel extracts of Irvingia wombolu on metabolic disorders in streptozotocin-induced diabetic rats

Abstract: Background Diabetes is widely recognized as associated with several structural and functional liver, kidney, and heart abnormalities. Therefore, the present study was conducted to evaluate the protective effect of peel extracts of Irvingia wombolu against diabetes complications. Methods Diabetes was induced by intravenous administration of streptozotocin (STZ) (50 mg/kg) through the right jugular vein on rats and animals with blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…This positive influence of fruits in human health is attributed to natural antioxidant phytochemicals inherent in them (Venket Rao et al, 2013). Interestingly, Matsinkou et al (2012) showed that I. wombulu seeds possess antioxidant phytochemicals. Phytochemicals such as alkaloids, saponins and tannins have been shown to be very important in agriculture; known to protect plants against microorganisms, and also possess allelopathic properties (Matsinkou et al, 2012;Boakye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This positive influence of fruits in human health is attributed to natural antioxidant phytochemicals inherent in them (Venket Rao et al, 2013). Interestingly, Matsinkou et al (2012) showed that I. wombulu seeds possess antioxidant phytochemicals. Phytochemicals such as alkaloids, saponins and tannins have been shown to be very important in agriculture; known to protect plants against microorganisms, and also possess allelopathic properties (Matsinkou et al, 2012;Boakye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%